Analisis Perbandingan Persepsi dalam Perumusan Kebijakan Luar Negeri antara Moon Jae In dan Yoon Suk Yeol terhadap Aliansi Pertahanan Korea Selatan – Amerika Serikat Tahun 2017-2022 - Tasya Aryanti Santoso; Aditya Maulana Hasymi; Yoga Suharman; Seftina Kuswardini (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2023)
This study compares the perceptions of foreign policy of the two South Korean leaders, Moon Jae In and Yoon Suk Yeol. The comparison of perceptions leads to the continuation of the defense alliance cooperation with the United States. The political transition is very visible in the two figures in building the progress of cooperation. Moon is known as a liberal-leaning political figure with a humanist style, so he is careful to establish two-way cooperation with the United States and North Korea to avoid threats to security stability in the region. Meanwhile, Yoon Suk Yeol is better known as a leader who represents conservatives as his political principle. Yoon is showing more aggressiveness to increase military strength with the United States in the face of North Korea's possession of nuclear weapons. This study uses the theory of Ole R. Holsti to understand the foreign policy perceptions of each figure which leads to output as foreign policy. There are three components to form a perception scheme in foreign policy, namely information, belief system, and perception. This study found that there are party interests and paradigm values in the belief system that have a strong influence in shaping the perceptions of Moon Jae In and Yoon Suk Yeol. This analysis also shows the contrast between regime shifts which show that both of them have a closed image and there is resistance to the continuation of policies in the previous regime so that the alliance cooperation with the United States experiences dynamics.